Immobilization and evacuation of accident victims by first responders in Delhi, India: a survey - Joseph, Teena Elsa; Sharawat, Rajesh; Phadke, Vandana; Acharya, Smita Chakraboraty; Sachdev, Gaurav; Chhabra, Harvinder Singh (International Journal Of Community Medicine And Public Health, 2021)
Background: Despite many improvements, pre-hospital care is known to be inconsistent and inefficient across India. This contributes to high mortality and morbidity of accident and medical emergency victims. Pre-hospital care may be provided by bystanders, but they are known to hesitate due to multiple reasons. The first aiders (ambulance staff or police personnel) who are responsible for providing appropriate initial care are not adequately trained to manage all aspects of emergency situations including extrication, cardiopulmonary resuscitation, management of bleeding, and protection of the spine evacuation and transfer. The current study was conducted to gauge the knowledge of first aid among bystanders and first aiders in Delhi national capital region. Methods: Two separate surveys with closed-ended questions were formulated for the bystanders and first aiders in english and hindi. A sample of 511 bystanders and 309 first aiders (108 ambulance and 201 police personnel) completed the survey between February 2019 and April 2019. Data was analysed descriptively. Comparison were made across demographic variables for the bystanders. For first aiders, comparisons were made between ambulance staff and police personnel, and between emergency medical technicians and drivers. Results: The average total scores for the bystanders were 38.5±14.2%. Slight differences across age and educational qualifications were found. The average total score for the first aiders was 34.3±12.3%. Ambulance personnel scored significantly better than police personnel in evacuation (70.3±26.6% versus 42.6±26.5%) and CPR subdomains (37.6±19.4% versus 21.9±14.7%). The emergency medical technicians scored better than the driver in their total and first aid subdomain scores. Conclusions: The knowledge amongst first responders including bystanders and first aiders was low and efforts to educate and train them would improve the much-needed quality of pre-hospital care.